The use of the amber necklace in babies: Literature review - Hidalgo-Mora, Elizabeth (2023)
Objective: To collect updated information based on scientific evidence on the use of the amber necklace in babies. Material and Methods: TA search strategy was carried out in the bibliographic databases such as MEDLINE (Pubmed), SCOPUS, EMBASE, LILACS, Scielo and Google Scholar (Grey literature) using the descriptors "Amber", "Succinic Acid", "Primary Tooth", "Dental Eruption" and "Local Symptoms". Articles published between 2012 and 2022 in English, Portuguese and Spanish were included, which addressed issues related to the use of the amber necklace in babies, considering the benefits and/or negative effects. Literature reviews, book chapters and theses were excluded. A total of 6 articles were included. Conclusion: AThe use of the amber necklace in babies is focused on the control of the symptoms of dental eruption. However, there is still no scientific evidence to confirm its efficacy. The negative effects of wearing the amber necklace are bacterial contamination, strangulation, and lack of safety in its use. Dentists should contraindicate its use in babies since there is no scientific evidence to support the use of amber necklade to control the symptoms of dental eruption in babies.